Investigating the Dynamic Nexus between Non-Oil Taxes and Economic Growth in Nigeria: An ARDL Approach - Oghuma, Richard Iyere; Eluyela, Damilola Felix; Iyoha, Francis O. (International Journal of Energy Economics and Policy, 2022)
This paper examines the dynamic nexus between non-oil taxes and economic growth in Nigeria. The volatile nature of oil prices has threatened the balance and stability of public expenditure and the budgetary system as a tool for stimulating growth in Nigeria, hence the motivation to look into the prospects of the non-oil sector as a driver of growth. Secondary data covering the period 1994-2019 was used for this study. This period is selected to ensure that there are no missing data especially for VAT which began in 1994, therefore, using earlier periods will introduce missing data into the estimation. Standard time series econometric techniques were utilized in the study such as descriptive analysis, unit root testing, co-integration test and granger causality testing. The Autoregressive distributive lag model (ARDL) was then employed in the model estimation. The long-run results show the effect of non-oil taxes on economic growth in Nigeria and observed that the effect of log (VAT) on economic growth is negative. Specifically, the result indicates that an increase in VAT revenue by 1% results in decline in GDP by about 0.21% and the result is significant at 5%. In the case of CED, the result shows that the economic growth is impacted positively. Specifically, a 1% rise in CED revenue stimulates growth by 0.113%, and the result is significant at 10%. Also, the effect of PIT revenue on growth is negative and significant at 5% and specifically, a 1% increase in PIT revenue results in decline in economic growth by 0.599%. The result shows that CIT has a positive impact on economic growth, and it is significant at 5%. This implies that a 1% increase in CIT revenue increases economic growth by 0.5757%. The findings of the above have the following implications. First, the negative effect of PIT and VAT on growth suggests that there is a need for fiscal authorities to re-examine these taxes and hence high VAT and PIT rates may be counter-productive for growth. Secondly, CIT and CED show positive growth effects and hence there is a need for effective and accountable expenditure framework that will ensure optimization of public expenditure in this regards.